The Impact of Tourism Activities on Environmental Conditions in the Gunung Puteri Lembang Area - Sri Ratna Wulan; Puspita Purna Wahyuni; Sinta Bela (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of nature-based tourism in forest areas has shown a significant increase in recent years, including in the Gunung Puteri Lembang area. Tourism activities such as camping and trekking provide economic benefits for local communities; however, they also exert pressure on environmental conditions. This study aims to analyze the impact of tourism activities on environmental conditions in the Gunung Puteri Lembang area. The research method employed is a descriptive qualitative approach, utilizing field observations, documentation, and literature review. The results indicate that tourism activities have positive impacts, including increased local income and community involvement in area management. However, significant negative impacts are also identified, such as soil compaction, erosion, waste pollution, noise which potentially reduce environmental quality and the ecological functions of the forest. Based on these findings, it can be concluded that tourism activities in Gunung Puteri have both positive and negative impacts, highlighting the need for management based on ecotourism principles and environmental carrying capacity to ensure the sustainability of the area.